Amministrazione pubblica e diritti fondamentali (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Libertà e diritti fondamentali - 2. Amministrazione e diritto alla salute - 3. Amministrazione e diritto all'unità familiare, all'istruzione e alle prestazioni sociali - 4. Amministrazione e diritto di proprietà - 5. Per una effettività dei diritti fondamentali attraverso l'amministrazione.Public Administration and Fundamental RightsABSTRACT: Moving from a brief historical reconstruction, the present contribution examines the theme of fundamental rights, focusing in particular on those that are ultimately the subject of profound debate, such as the right to health, especially due to the implications it presents with other highly discussed issues such as, for example, the end-of-life, as well as the right to family unity, with particular reference to foreigners. He also pauses to analyze more traditional fundamental rights such as the right to property and the right to education.